Dissemination of the Importance of Medical Record Review for Improving the Quality of Health Information at RSU 'Aisyiyah Padang - Dewi Oktavia (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
All healthcare facilities are required to maintain medical records. Recording of patient medical record documents can be used as health maintenance and patient treatment, evidence for law enforcement, education, and research, the basis for payment of health care costs, and health statistics data. Hospitals need to continue to improve service quality and patient safety on an ongoing and sustainable basis. To improve the quality of service, hospitals must be accredited periodically at least once every 3 (three) years, according to the mandate of Law Number 44 of 2009 concerning hospitals. Standards related to medical records in SNARS Edition 1 are in the hospital management standard group, namely medical record information management regarding the processing of medical record documents including preparation, filling in medical records, and reviewing medical records. Purpose : this service is to provide socialization regarding the importance of reviewing medical records at the 'Aisyiyah Padang General Hospital. Method : This Community Service Activity method is carried out by providing socialization and training on the importance of reviewing medical records to improve the quality of health information at 'Aisyiyah General Hospital Padang. Result: Implementation of community service activities that have been carried out at RSU 'Aisyiyah Padang went smoothly. Community Service (PKM) was held on October 6 and 7 2022 at 'Aisyiyah Hospital Padang Padang. All participants were enthusiastic about participating in the question-and-answer discussion. The PKM team also gave prizes/door prizes to 2 (two) participants who got the highest scores from giving quiz questions related to the material that had been presented. Conclusion : This activity is hoped that it will be able to increase the level of knowledge of health workers at RSU 'Aisyiyah Padang about the importance of reviewing medical records so that they can improve the quality of patient health information.